Π–π Interactions: Influence on Molecular Packing and Solid‐State Emission of ESIPT and non‐ESIPT Motifs. Issue 7 (27th June 2016) - Padalkar, Vikas S.; Sakamaki, Daisuke; Kuwada, Kenji; Horio, Akifumi; Okamoto, Haruka; Tohnai, Norimitsu; Akutagawa, Tomoyuki; Sakai, Ken‐ichi; Seki, Shu
Abstract: Novel, triphenylamino benzothiazole‐based excited‐state intramolecular proton transfer (ESIPT) and non‐ESIPT fluorophores were prepared by Suzuki coupling reactions. Their photophysical properties in solution, aqueous suspension, and in the solid state were systematically investigated. High fluorescence quantum efficiencies ( Φ sol ≈95 %; Φ solid ≈88 %), moderate Stokes shifts (≈8000 cm −1 ), microenvironment‐sensitive and molecular‐framework‐dependent emission are the striking features of the protocol described here. Solid‐state emission was modulated and interpreted as a crossover effect of π–π interactions using single‐crystal X‐ray analyses. The nonplanar/twisted framework of the system helps to avoid noncovalent interactions, facilitating the suppression of fluorescence quenching in the solid state with high quantum efficiency over 88 %. Abstract : Pack your things and glow ! The influence of molecular packing on the solid‐state emission properties of excited‐state intramolecular proton transfer and non‐excited‐state intramolecular proton transfer motifs is investigated in detail using synthetic, spectroscopic and single‐crystal X‐ray techniques.